Меч, дорога и удача: [роман] / Алекс Орлов - Орлов Алекс (Русский фантастический боевик, 2009)
Экземпляры: Аб (20140424) / Инвентарный номер: 101098 / Цена: 100.00 / Авт.знак: О-66 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6